Kebijakan Import saat Kondisi Inflasi - Nonius Apriliano; Hannaan Nabih Krisna; Zahra Radhina; Anna Charlita Lay (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Inflation is a complex economic phenomenon and has a broad impact, including on a country's import policy. When inflation occurs, domestic prices of goods and services increase, thereby increasing production and consumption costs. As a result, producers must increase product prices to maintain profit margins, which can reduce domestic demand and increase demand for imports because local prices become more expensive than imported goods. In addition, inflation also weakens the value of a country's currency, increases the demand for foreign exchange to pay for imports, and worsens the exchange rate. Countries with high inflation rates often experience trade deficits due to a surge in imports and a decline in exports, which in turn depletes foreign exchange reserves because they are needed to pay foreign debt and import goods that are needed but can no longer be exported. To overcome inflation, countries can adjust their strategies. import with more effective measures. Several steps that can be taken include: (1) Optimizing the Import List, namely prioritizing essential goods that are difficult to re-export; (2) Negotiation of Import Tariffs, with the aim of reducing import costs and increasing trade flexibility; and (3) Investment in the Local Manufacturing Sector, in order to reduce dependence on imports and increase domestic competitiveness. With this strategy, import policies can be anticipated and prepared proactively to be more effective in dealing with inflationary conditions. This abstract discusses the impact of inflation on import policies and strategies to deal with it, such as optimizing import lists, negotiating import tariffs, and investing in the local manufacturing sector.